Software project management in a changing world - Ruhe, Günther; Wohlin, Claes (Springer, 2014)
By bringing together various current directions, Software Project Management in a Changing World focuses on how people and organizations can make their processes more change-adaptive. The selected chapters closely correspond to the project management knowledge areas introduced by the Project Management Body of Knowledge, including its extension for managing software projects. The contributions are grouped into four parts, preceded by a general introduction. Part I “Fundamentals” provides in-depth insights into fundamental topics including resource allocation, cost estimation, and risk management. Part II “Supporting Areas” presents recent experiences and results related to the management of quality systems, knowledge, product portfolios, and global and virtual software teams. Part III “New Paradigms” details new and evolving software-development practices including agile, distributed, and open and inner-source development. Finally, Part IV “Emerging Techniques” introduces search-based techniques, social media, software process simulation and the efficient use of empirical data, and their effects on software-management practices. This book will attract readers from both academia and practice with its excellent balance between new findings and experience of their usage in new contexts. Whenever appropriate, the presentation is based on evidence from empirical evaluation of the proposed approaches. For researchers and graduate students, it presents some of the latest methods and techniques to accommodate new challenges facing the discipline. For professionals, it serves as a source of inspiration for refining their project-management skills in new areas
Includes bibliographical references and index
Keywords: Projektmanagement; Softwareentwicklung